2023
DOI: 10.3389/fnume.2023.1078536
|View full text |Cite
|
Sign up to set email alerts
|

A heterogeneous phantom study for investigating the stability of PET images radiomic features with varying reconstruction settings

Abstract: The purpose of this work was to assess the capability of radiomic features in distinguishing PET image regions with different uptake patterns. Furthermore, we assessed the stability of PET radiomic features with varying image reconstruction settings. An in-house phantom was designed and constructed, consisting of homogenous and heterogenous artificial phantom inserts. Four artificially constructed inserts were placed into a water filled phantom and filled with varying levels of radioactivity to simulate homoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…Although image reconstruction shows varying effects on the stability of radiomic features, the study by Shiri et al . has shown that first-order entropy is robust against different reconstruction settings, which is consistent with the results of our study [53,56].…”
Section: Discussionsupporting
confidence: 93%
“…Although image reconstruction shows varying effects on the stability of radiomic features, the study by Shiri et al . has shown that first-order entropy is robust against different reconstruction settings, which is consistent with the results of our study [53,56].…”
Section: Discussionsupporting
confidence: 93%